2017
DOI: 10.1002/hep.29112
|View full text |Cite
|
Sign up to set email alerts
|

Sodium taurocholate cotransporting polypeptide is the limiting host factor of hepatitis B virus infection in macaque and pig hepatocytes

Abstract: Ntcp is the key host factor limiting HBV infection in cynomolgus and rhesus macaques and in pigs. In rodents (mouse, rat) and dogs, transfer of hNTCP supports viral entry but additional host factors are required for the establishment of HBV infection. This finding paves the way for the development of macaques and pigs as immunocompetent animal models to study HBV infection in vivo, immunological responses against the virus and viral pathogenesis. (Hepatology 2017;66:703-716).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 39 publications
8
82
1
Order By: Relevance
“…Currently, primary human hepatocytes (PHHs) (Lempp et al, 2017;Ni and Urban, 2017;Shimura et al, 2017), HepaRG cells (Gripon et al, 2002;Schulze et al, 2012), and primary tupia hepatocytes (PTHs) (Kock et al, 2001;Ren and Nassal, 2001) are the main cell models used to study the early steps of HBV infection. PHHs, the natural host of HBV, are regarded as the ideal cellular model for HBV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, primary human hepatocytes (PHHs) (Lempp et al, 2017;Ni and Urban, 2017;Shimura et al, 2017), HepaRG cells (Gripon et al, 2002;Schulze et al, 2012), and primary tupia hepatocytes (PTHs) (Kock et al, 2001;Ren and Nassal, 2001) are the main cell models used to study the early steps of HBV infection. PHHs, the natural host of HBV, are regarded as the ideal cellular model for HBV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Human NTCP as well as the rat, mouse, and dog orthologs efficiently bound Myrcludex‐B, while macaque and pig NTCP did not. However, only hNTCP was able to confer efficient HBV and HDV infection . Taken together these data suggest that only hNTCP is able to confer HBV and HDV entry and that hepatocytes from distinct species lack an additional essential entry factor or express a species‐specific restriction factor.…”
Section: Features Of Hbv and Hdv Infection In Primary Hepatocytes Fromentioning
confidence: 77%
“…A key finding of this study is the observation that primary hepatocytes from macaque (cynomolgus and rhesus) and pig become fully susceptible to both HDV and HBV infection when transcomplemented with hNTCP . Although viral replication appeared to be lower than in human hepatocytes, it was robustly detectable including formation of covalently closed circular DNA .…”
Section: Features Of Hbv and Hdv Infection In Primary Hepatocytes Fromentioning
confidence: 81%
See 1 more Smart Citation
“…In vitro studies have suggested that hNTCP expression in primary hepatocytes from cynomolgus macaques, rhesus macaques, and pigs render these cells susceptible to hepatitis delta virus (HDV) and presumably HBV infection and replication . This concept was recently tested in vivo for macaques.…”
Section: Discussionmentioning
confidence: 99%